Irishness and Racism: Towards an E Reader - LENTIN, RONIT (My University, 2006)
The article is partly annotated bibliography, partly resource collection, partly review and partly programme of action on the nexus of racism, ethnicity and Irishness. As befits an e-journal, the article provides accessible links to appropriate web-based organisations or resources. The work of the authors in this area ? particularly the edited collection Racism and Anti-Racism in Ireland (2002) ? was an attempt to fill a theoretical and pedagogical gap in speaking about the specificities of racism in the Irish context. The article argues that making sense of the dialectic between continuity and change is the key to understanding the dynamics of racism in the new millennium. In consequence we need to theorise and resist two apparently contradictory trends ? globalisation and the strengthening in of the racist state. These are at the very core of the nexus of Irishness and racism.
PUBLISHED
Keywords: Sociology